ChemInform Abstract: Iridium‐Catalyzed Chemoselective Reductive Nucleophilic Addition to N‐Methoxyamides. Issue 34 (August 2015) - Nakajima, Minami; Sato, Takaaki; Chida, Noritaka
Abstract The reaction tolerates a broad range of substituents on the N‐methoxyamides.